2000
DOI: 10.1063/1.874028
|View full text |Cite
|
Sign up to set email alerts
|

A model of laser imprinting

Abstract: An analytical model is developed to gain physical insight of the laser imprint Summary • Laser nonuniformities imprint surface modulations that degrade the symmetry of implosion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 32 publications
1
64
1
Order By: Relevance
“…This is called laser imprint, which also causes a RTI seed in ICF implosion (Emery et al 1991;Ishizaki & Nishihara 1997Taylor et al 1997;Nishihara et al 1998;Matsui et al 1999;Goncharov et al 2000;Velikovich et al 2000). A rippled shock wave and ablation surface deformation caused by non-uniform laser irradiation on a smooth target were also evaluated with the deflagration model (Ishizaki & Nishihara 1997).…”
Section: (E) Rm-like Instabilities and Ablative Rmimentioning
confidence: 99%
See 3 more Smart Citations
“…This is called laser imprint, which also causes a RTI seed in ICF implosion (Emery et al 1991;Ishizaki & Nishihara 1997Taylor et al 1997;Nishihara et al 1998;Matsui et al 1999;Goncharov et al 2000;Velikovich et al 2000). A rippled shock wave and ablation surface deformation caused by non-uniform laser irradiation on a smooth target were also evaluated with the deflagration model (Ishizaki & Nishihara 1997).…”
Section: (E) Rm-like Instabilities and Ablative Rmimentioning
confidence: 99%
“…Another stabilization mechanism in ablative RMI, called dynamic overpressure, is discussed in Goncharov (1999) and Goncharov et al (2000), in which the sharp-boundary model (SBM) was used instead of the deflagration model. The SBM was originally developed to study ablative RTI (Piriz et al 1997).…”
Section: (E) Rm-like Instabilities and Ablative Rmimentioning
confidence: 99%
See 2 more Smart Citations
“…Simulations have shown that laser imprint occurs primarily during the low intensity foot pulse. 7,8 A long scale buffering plasma forms during the higher intensity main pulse that smoothes the effects of laser illumination nonuniformity. The relatively cold (50-100eV) plasma that forms during the foot pulse does not have sufficiently good electron thermal conductivity between the target and the laser absorption region to allow such long scale plasmas to form.…”
Section: Introductionmentioning
confidence: 99%